Belt and road initiative: how could Canadian business get involved? - Wei, William (Henry Stewart Talks, 2018)
The Belt and Road Initiative (BRI), BRI: opportunities for Canadian business, Trade volume along the Belt and Road, Proportion of China FDI stock in BRI countries, The Asian Infrastructure Investment Bank (AIIB), Potential risks